Kindergarten Teacher's Paradigm Against Problems That Often Arise In Learning: The Perspective of Early Childhood - Saputra, Tohari; Pamungkas, Abdul Harits; Bilchoir; Septriani, Nimas (International Journal of Education and Teaching Zone, 2023)
This study aims to analyze the teacher's paradigm of problems in learning from the perspective of early childhood. This type of research is descriptive qualitative. The subject of this research is Nur Toyyibah Kindergarten in Eka Jaya, Jambi City. The population in this study were all teachers who taught at Nur Toyyibah Kindergarten, totalling five people. In contrast, the sample in this study was four teachers at Nur Toyyibah Kindergarten, where the sample was taken using the kurtosis sampling technique. The data collection technique was carried out using a multilevel interview technique where the results of the interviews were. Learning will be carried out from the most frequent to the lowest. The results of the study showed that the problem that often arises in learning in early childhood based on the teacher's paradigm is a fixation on the use of mobile phones. The use of mobile phones is the most common thing in early childhood at Nur Toyyibah Kindergarten.